Diagnostic Evaluation of Multiplex Real Time PCR, GeneXpert MTB/RIF Assay and Conventional Methods in Extrapulmonary Tuberculosis - Sanjay Singh Negi; Priyanka Singh; Sachin Chandraka; Ujjwala Gaikwad; Padma Das; Anudita Bhargava; Ajoy Behra; Nitin M Nagarkar (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Effective management of Extrapulmonary Tuberculosis (EPTB) requires simultaneous identification of Mycobacterium tuberculosis (M.tuberculosis) complex, NonTuberculous Mycobacteria (NTM) and Rifampicin (RIF) sensitivity pattern for early and effective evidence based Antitubercular Treatment (ATT). Aim: To evaluate the diagnostic potential of multiplex Real-Time Polymerase Chain Reaction (mRT-PCR) versus GeneXpert and conventional microscopy and culture. Materials and Methods: A total of 110 multivaried extrapulmonary specimens from an equal number of patients with strong clinical/radiological/histopatholgical evidence of EPTB were subjected to conventional microscopy, liquid culture MGIT 960 system, GeneXpert and mRT-PCR. Results: Highest positivity of 88.8% (97/110) was shown by mRT-PCR followed by GeneXpert (52.72%, 58/110), liquid culture MGIT 960 system (44.54%, 49/110) and microscopy (4.54%, 5/110), (p<0.01, χ2 =156). Comparing it with culture positive cases (n=49), the sensitivity, specificity, Positive and Negative Predictive Value (PPV and NPV) of GeneXpert was found to be 87.25%, 100%, 100% and 80.64% respectively while the same parameters were 100% each for mRT-PCR. mRT-PCR showed higher positivity over GeneXpert in various individual extrapulmonary sample category with significant difference seen in synovial fluid. The specific added advantage of mRT-PCR was seen in the detection of 17 NTM. GeneXpert advantage seen in detection of five cases of RIF resistance. Conclusion: With individual feature of detection of NTM by mRT-PCR and RIF resistance by GeneXpert, this study may advocate the use of mRT-PCR adjunct to GeneXpert in the diagnostic armamentarium to identify more rapidly and effectively both M.tuberculosis and NTM along with RIF resistance information for early and specific ATT intervention of all EPTB cases including Multi Drug Resistant (MDR). However, further research may be required to enhance the sensitivity of both GeneXpert and mRT-PCR to exclude all possibilities of false negative EPTB cases.